2022
DOI: 10.1021/acsnano.2c00945
|View full text |Cite
|
Sign up to set email alerts
|

On-Surface Debromination of C6Br6: C6 Ring versus C6 Chain

Abstract: Carbon allotropes comprising sp-hybridized carbon atoms have been investigated for decades for their molecular structure. One of the unsolved mysteries is whether they should take a linear or cyclic configuration in condensed phases due to the lack of atomistic characterizations. Herein, we designed a molecule with a C6 skeleton as a model system to address this issue, which was achieved by eliminating Br atoms from hexabromobenzene (C6Br6) molecule on the Ag(111) substrate via thermal treatment. It is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…3e), where individual ones could be identified as indicated by the green contours. As inspired by the previous studies 4,12 and compared with STM observations, 4,6 we attributed the three central bright protrusions to Ag atoms, connecting three neighboring dibrominated components. The large-scale STM images of islands composed of organometallic dimers and trimers are also provided in Fig.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…3e), where individual ones could be identified as indicated by the green contours. As inspired by the previous studies 4,12 and compared with STM observations, 4,6 we attributed the three central bright protrusions to Ag atoms, connecting three neighboring dibrominated components. The large-scale STM images of islands composed of organometallic dimers and trimers are also provided in Fig.…”
mentioning
confidence: 69%
“…1 It has also attracted great attention from the surface science community as a versatile strategy to construct C-C bonds and corresponding carbon-based nanoarchitectures via on-surface synthesis. 2 Moreover, by means of in situ characterization techniques, such as scanning tunneling microscopy (STM) and atomic force microscopy (AFM), 3 sets of intermediates, generally classified into surface-stabilized radicals and organometallic intermediates, have been successfully captured on surfaces and visualized in real space, [4][5][6] which is usually a great challenge in traditional organic synthetic chemistry. As early as 2000, Hla et al reported deiodination and sequential coupling processes (i.e., Ullmann reaction) on surface with all elementary steps controllably triggered by STM tip manipulations and intermediates captured.…”
mentioning
confidence: 99%
“…Second, the herringbone reconstruction of Au(111) can be lifted by adsorbate-induced stress modification, , which in turn makes an impact on the molecular assembly . Third, Au(111) is the least reactive noble metal for Ullmann coupling that prevents the decomposition of organic skeletons before desorption. , In this study, we reveal that hot dosing a trace amount of HBB onto a preheated Au(111) surface results in QCs defined by barriers built from Br dot chain arrays. The chain arrays aggregate into highly stable QCs with an average pore size of 3.7 ± 0.1 nm, which is confined by triangular soliton walls formed from Au(111) surface reconstruction induced by the strong bonding of Br with thermal treatment.…”
mentioning
confidence: 74%
“…To this end, we use hexabromobenzene (HBB) and Au(111) as the precursor and substrate to construct robust QCs with high-yield production (Scheme ). Our approach is based on the following experimental facts: First, the dehalogenation reaction is appealing for on-surface synthesis of covalently linked architectures with atomic precision. ,, The byproducts, Br adatoms, bind strongly on the Au(111) surface that can only be desorbed above 720 K in the absence of other species . Second, the herringbone reconstruction of Au(111) can be lifted by adsorbate-induced stress modification, , which in turn makes an impact on the molecular assembly .…”
mentioning
confidence: 99%
“…For example, the heterocyclic ring-opening reactions, such as on-surface desulfurization of thiophene, deconstruction of porphyrin and N -doped nanographene, and the ring-opening polymerization of melamine, have been reported to generate a variety of novel nanostructures. Recently, Gao et al reported a debromination ring-opening coordination reaction of hexabromobenzene to synthesize C6–Ag organometallic polyyne …”
Section: Introductionmentioning
confidence: 99%